Correlates of anomia in non-semantic variants of primary progressive aphasia converge over time. (November 2019) - Leyton, Cristian E.; Landin-Romero, Ramon; Liang, Cheng Tao; Burrell, James R.; Kumfor, Fiona; Hodges, John R.; Piguet, Olivier
Abstract: To track neural correlates of naming performance with disease progression, we estimated key areas affected in nonfluent/agrammatic (nfvPPA) and logopenic (lvPPA) primary progressive aphasia variants over time and changes in naming correlates over time. Twenty-nine non-semantic PPA participants (17 nfvPPA and 12 lvPPA) were selected based upon current diagnostic criteria and PiB-PET status and conducted a confrontation-naming task and a structural MRI. Linear mixed-effect models implemented in FreeSurfer were used for tracking cortical thickness and epicenters of atrophy over time. Using averaged cortical thickness of epicenters and naming performance as variables of interest, two sets of multivariate analyses were conducted to compare atrophy progression and naming correlates across groups. While all PPA participants demonstrated naming deterioration and progressive cortical thinning in the left temporal lobe and the left inferior frontal gyrus, the lvPPA cohort showed greater naming deterioration and thinning in the left posterior inferior parietal cortex over time than it did the nfvPPA cohort. The multivariate analyses confirmed a widespread cortical thinning in lvPPA over time, but a more rapid thinning in the right superior frontal gyrus of nfvPPA participants. Impaired naming correlated with common cortical regions in both groups. These regions included the left anterior superior temporal gyrus and the posterior middle temporal gyrus, which was primarily affected in lvPPA. Non-semantic PPA variants initially present with separate epicenters of atrophy and different spatial-temporal patterns of neurodegeneration over time, but the common involvement in key cortical regions of the left temporal lobe accounts for naming deterioration in both groups.